Penerapan Konsep Community Based Tourism (CBT) dalam Pengelolaan Desa Wisata Sebagai Upaya Peningkatan Perekonomian Masyarakat - Meri Anti Khusnawati; Amin Wahyudi (STIEPAR YAPARI Bandung, 2023)
Tourism villages are one of the most developed tourism in Indonesia, because they have supporting potentials. This research aims to determine the development of tourism villages with the concept of community-based tourism and the impact of the existence of these tourism villages on the community. The method used in this study is literature study. Library research is research that formulates theoretical and methodological contributions to a particular issue and critically examines the ideas found in the literature. The use of the CBT concept in tourism village management has a huge influence, especially on the economy of the local community. The presence of tourism villages can provide benefits to the surrounding environment by opening up job opportunities. The income obtained from the tourism industry can improve the standard of living of local people. In maintaining the attractiveness of tourist destinations for visitors, tourism village management requires continuous innovation, such as creating new tourism destinations, holding festivals and other cultural events, and improving service facilities.